Enhanced temperature stability and exceptionally high electrical contrast of selenium substituted Ge2Sb2Te5 phase change materials. Issue 28 (20th March 2017) - Koch, Christine; Hansen, Anna-Lena; Dankwort, Torben; Schienke, Gerrit; Paulsen, Melf; Meyer, Dominik; Wimmer, Martin; Wuttig, Matthias; Kienle, Lorenz; Bensch, Wolfgang
Abstract : Compared to the pure telluride Ge2 Sb2 Te5, Ge2 Sb2 Te4 Se (I) and Ge2 Sb2 Te2 Se3 (II) thin films reveal an exceptionally large electrical contrast (increased by factor 100 for compound II) between the amorphous and crystalline phases. Abstract : Ge2 Sb2 Te4 Se (I) and Ge2 Sb2 Te2 Se3 (II) thin films were synthesized and compared to the pure telluride Ge2 Sb2 Te5 . In situ X-ray diffraction (XRD) and in situ transmission electron microscopy (TEM) investigations revealed a remarkably increased stability of the as-deposited amorphous phase. The transition temperature (beginning transition) determined with in situ XRD increases from 135 °C for the pure telluride to 165 °C for (I) and to 225 °C for (II). An identical trend for the transition temperatures (transition complete) was observed by sheet resistance measurements with values of 153, 190 and 243 °C, respectively. Optical properties determined with Fourier-transform-infrared (FTIR) spectroscopy and variable incident angle spectroscopic ellipsometry (VASE) exhibit a significant energy-dependent behavior of the dielectric functions. Major changes of the maxima and intensities of the extinction coefficients and the indices of refraction are observed with increasing Se content. These results are in agreement with the results obtained by Rietveld refinement and TEM. The incorporation of Se into the structure of the metastable cubic phase causes small distortions, leading to a phase transition. Electrical sheet resistance measurements reveal an exceptionally large electrical contrast between the amorphous and crystalline phases, which is increased by a factor of 100 for compound (II) compared to established phase change materials.